Improving the Security of ChaCha against Differential-Linear Cryptanalysis - Coutinho, Murilo; Passos, Iago; Sousa Jr., Rafael T. de; Borges, Fábio (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2020: Anais do XX Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2020.19224, 2020)
The stream cipher ChaCha has received a lot of attention and recently is being used as a new cipher suite in TLS 1.3, as a random number generator for operating systems (Linux, FreeBSD, OpenBSD, NetBSD, and DragonFly BSD), a proposed standardization in RFC 7634 for use IKE and IPsec, and by the WireGuard VPN protocol. Because of that, it is very important to understand and study the security of this algorithm. Previous works showed that it is possible to break up to 7 of the 20 rounds of ChaCha. In this paper, we show that a simple modification in the algorithm, namely changing the rotation distances in the Quarter Round Function, makes ChaCha more secure against all the most effective known attacks without any loss in performance. In fact, we show that with these changes, it is only possible to break up to 6 rounds of ChaCha. Therefore, it would be no longer possible to break 7 rounds of ChaCha with the best-known attacks.